A cyber-consumer protection framework for prevention of online deceptive advertising - Al Adwan, Ahmad (Curtin University, 2012)
Online deceptive advertisements engender distrust among cyber-consumers; we found that such incidents occur in every country in the world. This research addressed issues with online fraud and deceptive advertising related to cyber-consumer transactions (CCT) and online consumer protection. This study includes a framework which provides potential solutions and redress methods in order to minimise online fraud and deceptiveness as well as protecting the cyber-consumer globally.